2019
DOI: 10.18499/2070-478x-2019-12-4-274-281
|View full text |Cite
|
Sign up to set email alerts
|

The choice of surgical treatment of inguinal hernia (literature review)

Abstract: Inguinal hernioplasty is one of the most common surgical procedures, but the long-term results of operations leave much to be desired: there are recurrences of hernias, chronic pain syndrome, violation of testicular function in men. A modern review of the literature on the most common surgical methods of treatment of inguinal hernias is presented. Separately, describes the methods of hernioplasty with using local tissue (autodermaplasty) and with the use of mesh implants (allohernioplasty). Material allohernio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In 2016, Ivanov [ 42 ] showed that the pathophysiology of hernia is caused by a lack of collagen production and an amino acid deficiency. A protein produced by leukocytes can trigger and activate the immune system against inflammatory responses such as hernias.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Ivanov [ 42 ] showed that the pathophysiology of hernia is caused by a lack of collagen production and an amino acid deficiency. A protein produced by leukocytes can trigger and activate the immune system against inflammatory responses such as hernias.…”
Section: Discussionmentioning
confidence: 99%